2020
DOI: 10.1111/psyp.13518
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of calorie‐related modulation of N2 in food‐related Go/No‐Go training: A preregistered ERP study

Abstract: Go/No‐Go tasks, which require participants to inhibit automatic responses to images of palatable foods, have shown diagnostic value in quantifying food‐related impulses. Moreover, they have shown potential for training to control impulsive eating. To test the hypothesis that training modulates early neural markers of response inhibition, the current study investigated how the N2 event‐related brain potential to high‐ and low‐calorie food images changes along Go‐/No‐Go training and how the N2 is related to late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…In line with this, three previous studies have investigated electrophysiological underpinnings of this phenomena but reached inconsistent conclusions ( van de Vijver et al. , 2018 ; Aulbach et al. , 2020 ; Carbine et al.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In line with this, three previous studies have investigated electrophysiological underpinnings of this phenomena but reached inconsistent conclusions ( van de Vijver et al. , 2018 ; Aulbach et al. , 2020 ; Carbine et al.…”
Section: Introductionmentioning
confidence: 92%
“…(2018) found that after a go/no-go training, larger increases in theta power at frontal midline electrodes were present upon presentation of food pictures previously associated with a no-go response. However, the two remaining studies showed that neither single session nor multiple sessions of a food-specific go/no-go training affected food-related N2 event-related potential (ERP) response (an indicator of inhibitory control processes) to go- or no-go trials after training ( Aulbach et al. , 2020 ; Carbine et al.…”
Section: Introductionmentioning
confidence: 99%
“…After screening the titles and abstracts of all the entries, 38 full texts were examined, but 17 were excluded because they did not meet the inclusion criteria. Thus, 21 articles were added for analyses to those already identified by Forcano et al 23 Among the 45 selected articles, 13,17,19,20,21,30–69 12 included multiple studies, we therefore considered the results of 61 studies, (mean sample size = 115.84, SD = 109.53; range = 18–561).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest an increased need for inhibitory control neural resources when inhibiting a response towards high-calorie foods. Similar to the N2, P3 amplitude becomes larger (i.e., more positive) when inhibiting towards high-calorie foods compared to low-calorie foods (see also Aulbach et al, 2020;Carbine et al, 2017;Carbine et al, 2018a), again suggesting increased cognitive control when inhibiting to high-calorie foods.…”
Section: Introductionmentioning
confidence: 82%